Environment-Based Creativity: Empowering Women Through Spunbond Bag Recycling Craft Training - Renny Candradewi Puspitarini; Novita Wulandari; Mulkan Andika Situmorang; Vivi Agustiani; Nike Widiastuti; Verto Septiandika; Mastina Maksin; Trismawati; Imam Sucahyo; Supriyanto; Andhi Nur Rahmadi; Eko Yudianto Yunus; Husni Mubarok (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Women's empowerment and environmental management are two important issues in sustainable development. Dharma Wanita Association (DWA) Probolinggo City responded to these two issues through creative training in making decorative flowers from used spunbond bags. This training aims to teach DWA members how to utilize spunbond bags, which often accumulate in households due to the policy to reduce the use of plastic bags, into economically valuable craft products. Apart from supporting policies to reduce plastic waste, this training also functions as a means of empowering women by increasing their skills and creativity in the field of handicrafts. The results of this activity are not only environmentally friendly decorative flower products, but also the potential for further development in the field of recycling-based crafts. This training opens up opportunities for participants to develop small businesses based on recycled products, as well as expand networks with other communities that support the waste management movement. In addition, the potential for this activity can be integrated with environmental education and adopted as a sustainable program to increase environmental awareness in society. With increasing awareness of the importance of protecting the environment, recycling-based training like this has bright prospects and can become a model for similar activities in the future. This activity not only provides economic and social benefits for DWA members, but also contributes to global efforts to reduce the negative impact of plastic waste on the environment.